Analysis of Knowledge Management Implementation on Employee Performance in the Rubber Tyred Gantry (RTG) Division of PT Prima Multi Peralatan - Kembaren, Eqy Gusti Immanuel Saor; Lumbanraja, Prihatin; Pohan, Vivi Gusrini Rahmadani (International Journal of Business and Applied Economics, 2024)
The objective of this study is to obtain empirical evidence and conduct an analysis of the impact of Knowledge Management Implementation on Employee Performance within the Rubber Tyred Gantry (RTG) Division at PT Prima Multi Peralatan. This research adopts a quantitative, survey-based approach employing an associative method. The study population consists of all employees within the RTG Division at PT Prima Multi Peralatan, located at the Belawan Container Terminal, totaling 58 individuals, with the sample size comprising the entire population (census sampling). Data collection was conducted directly by the researcher through observations, the administration of structured questionnaires, and the review of relevant documentation. This study employs a quantitative descriptive methodology, with data analysis designed to test the hypotheses and address the research questions posed. The data analysis was performed using Partial Least Squares – Structural Equation Modeling (PLS-SEM) with SmartPLS version 3 software.